Uncovering Gender Inequities: Bridging gender gaps in water access, control, and utilization among Borana Pastoralists in a changing climate - Firdissa, Selamawit; Alemayehu, Sintayehu; Workeneh, Sintayehu; Nchanji, Eileen Bogweh; Abdulhamid, Numery; Tesfaye, Lidya; Tegegne, Getachew; Kanno, Liyuneh; Ketema, Dessalegn Molla; Terefe, Tadesse; Doyo, Jaldesa (2025)
This study, undertaken as part of the Livestock Water Source Monitoring and Risk Management (LWSM) project, delves deeply into how entrenched gender norms influence the way water is accessed, controlled, and utilized within Borana pastoralist communities. It examines how societal expectations, customary practices, and cultural traditions shape the division of responsibilities between men and women-affecting not only who collects and manages water, but also who has the authority to make decisions about its allocation and use. By documenting these gendered patterns, the research reveals how they either enable or constrain individuals’ and households’ capacity to adapt to climate-related stresses. In doing so, it underscores the intricate and often invisible linkages between gender roles, local water management systems, and the broader culture of pastoral resource governance. The study further situates these relationships within the rapidly changing climate context of Borana, where recurrent droughts, shrinking water availability, and shifting rainfall patterns are placing unprecedented strain on both social systems and ecological resources. By highlighting these interconnections, the research offers critical insights into how gender-responsive water governance can strengthen adaptive capacity and resilience in a region highly vulnerable to climate shocks. Borana’s kebeles are predominantly livestock-based economies, complemented by small-scale farming and the production of milk, hides, and crafts. Women contribute significantly to the local economy through agricultural processing and sales yet have limited control over household and community resources. Social customs, while fostering strong communal ties, reinforce traditional gender divisions-men manage cattle, camels, and water sources, while women oversee sheep, goats, and domestic water needs. This division often restricts women’s access to key resources, decision-making, and climate adaptation opportunities. Water scarcity has intensified over the past five years due to unreliable water points and recurrent droughts, forcing households-particularly women and children-to travel long distances for water. Traditional community-managed water systems are under strain, and unsafe drinking water exacerbates health and productivity challenges. Climate shocks reduce livestock health, incomes, and food security, with women bearing the brunt as household managers and caregivers. Despite their central role in adaptation, women are often excluded from water management committees, limiting the impact of their innovations. The study stresses the need for inclusive governance, ensuring women’s participation in water resource management, and for investments in climate-resilient infrastructure. Expanding access to climate information, training, and diversified livelihood options-particularly through women’s associations and community networks-can strengthen resilience. Addressing restrictive gender norms and bolstering women-focused networks are key to fostering equitable access to water, improving livelihoods, and enhancing climate adaptability. By integrating gender-sensitive approaches, the LWSM project aims to help Borana communities overcome climate-related challenges while advancing social and economic equity.